CRITICAL BARRIERS OF FOOD SUPPLY CHAIN MANAGEMENT AND APPLICATION OF BLOCKCHAIN TECHNOLOGY TO MITIGATE THEIR IMPACTS - Patidar, Santosh; Sukhwani, Vijay Kumar; Shukla, Apratul Chandra (International Journal of Industrial Engineering: Theory, Applications and Practice, 2023)
Food safety and food security have captured the significant attention of researchers. The main objective of this study is to identify the critical barriers of food supply chain management in the Indian context. For this, a decision-making trial and evaluation laboratory (DEMATEL) based approach is used. With an assessment of existing literature and consultation with food chain experts, 15 barriers have been identified for analysis. Critical barriers and their causal relationships are explored through the cause-and-effect diagram. Results of this study show that the barriers, namely “Lack of Government policy and regulation support” (B8) and “Extreme & diverse climate conditions in India” (B15), are the top two most critical and influential barriers. Recent advances in Blockchain technology have paved for mitigating the impact of these barriers on the performance of the food supply chain, and with the suitable intervention of Blockchain technology, many such barriers can be overcome, thereby improving food supply chain performance.